A New Algorithm of Iterative MIMO Detection and Decoding Using Linear Detector and Enhanced Turbo Procedure in Iterative Loop - Bakulin, Mikhail; Kreyndelin, Vitaly; Rog, Andrey; Petrov, Dmitry; Melnik, Sergei (Proceedings of the XXth Conference of Open Innovations Association FRUCT, 2019)
In the paper we develop and evaluate a novel low complexity algorithm of iterative detection and decoding in multiple input multiple output (MIMO) system. It is based on a new enhanced Turbo procedure. Although the algorithm utilizes well-known components such as linear minimum mean square error (MMSE) detector and channel decoder with soft bits feedback, the new original procedure of getting extrinsic data essentially allows improving the receiver performance and reducing its complexity. Moreover, it is shown that proposed Turbo approach works even without channel decoder in the iteration loop. Thus, we ob-tain pure iterative MMSE detector with improved performance. Utilization of combined scheme with MMSE detector and channel decoder feedback demonstrates really outstanding performance. It is confirmed with simulations that the performance of proposed architecture exceeds traditional ML MIMO detector schemes that are designed with channel decoder but without iterative loop.